A semantic Case-Based Reasoning system to improve road safety. (15th May 2008) - Ceausu, Valentina
This paper presents a semantic Case-Based Reasoning (CBR) system designed to improve road safety. The system is based on the automatic exploitation of accident scenarios, a new road safety research tool. Accident scenarios describe prototypes of traffic accidents and point out the impact of the infrastructure for a particular accident prototype. Prevention measures concerning infrastructure engineering such as adapting the layout and use of road are provided for each accident scenario. Thereby, assigning real traffic accidents to accident scenarios allows us to establish road dysfunctions leading to accident. The system described in this paper provides an automatic solution to assign traffic accidents to accident scenarios by adopting a CBR approach.